Management :an Asia-Pacific perspective /John R. Schermerhorn Jr. ... [et al.] - Schermerhorn, John R.
"Authorised adaptation of the seventh edition by John R. Schermerhorn Jr, Management, published by John Wiley &Sons, New York, c2002" -- T.p. verso.